2003
DOI: 10.1046/j.1365-4362.2003.01708.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nickel patch test reactivity in phases of the menstrual cycle

Abstract: Estrogens not only impair the skin barrier but also have a negative impact on the immune system. Estradiol has been proved to suppress cellular immunity. In a few studies conducted to date, the relationship between phases of the menstrual cycle and the severity of patch test reactivity has been examined with equivocal results. In our study, we observed that the presence of reactions due to nickel sensitivity was independent of the phases of the menstrual cycle. Nevertheless, we would like to point out the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
3
17
0
1
Order By: Relevance
“…While some reports have shown that E2 enhances the Th2-type immune response, other reports have demonstrated that E2 enhances contact hypersensitivity (CHS) as a Th1-type immune response, and expression of interferon-γ (IFN-γ) as a Th1-type cytokine [5][6][7][8]. Human contact dermatitis, a Th1-type immune reaction, is more severe in the ovulation phase than in the luteal phase [5], while numerous experiments in mice have demonstrated that E2 enhances the production of IFN-γ [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some reports have shown that E2 enhances the Th2-type immune response, other reports have demonstrated that E2 enhances contact hypersensitivity (CHS) as a Th1-type immune response, and expression of interferon-γ (IFN-γ) as a Th1-type cytokine [5][6][7][8]. Human contact dermatitis, a Th1-type immune reaction, is more severe in the ovulation phase than in the luteal phase [5], while numerous experiments in mice have demonstrated that E2 enhances the production of IFN-γ [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Human contact dermatitis, a Th1-type immune reaction, is more severe in the ovulation phase than in the luteal phase [5], while numerous experiments in mice have demonstrated that E2 enhances the production of IFN-γ [6][7][8]. Hence, it has been suggested that E2 may enhance contact dermatitis by increasing IFN-γ production.…”
Section: Introductionmentioning
confidence: 99%
“…One case letter suggested that the outcome of patch testing could fluctuate with the menstruation cycle (339). However, other patch test studies have not confirmed this in series of nickel allergic patients (340–343). One recent Italian study by Bonamonte et al showed that the ovulatory phase of the menstruation cycle inhibited allergic responses in 30 nickel allergic subjects (344).…”
mentioning
confidence: 99%
“…(2,3) Contact hypersensitivity (CHS) in humans also is enhanced by E2. (4) However, the mechanism underlying the immunological actions of E2 has not been completely elucidated.…”
Section: Introductionmentioning
confidence: 99%